APAKAH TEORI PERKEMBANGAN KOGNITIF PIAGET BERLAKU DI INDONESIA? - siti hindun; Endang Toha Ruseffendi (UJMES (Uninus Journal of Mathematics Education and Science), 2018)
Research on students' cognitive development has been done in several other countries. But for research in Indonesia is still rarely done. This research uses survey method with qualitative approach. The purpose of this study is to describe an understanding concept of eternity number and concept of eternity length on elementary school students through the proof of cognitive development of Piaget's theory. The stage of cognitive development in this study is limited to the concrete operation phase. A total of 29 third graders participating in the study came from elementary schools with good quality in Indonesian education standards. The supporting instruments in this research are questionnaire and interview. The data collection is done by giving experiments about concept of eternity number and concept of eternity length presented in the questionnaire, and must be answered by the students along with the reason. Students' answers were analyzed descriptively on a percentage basis. Some cases that represent the results of the analysis, validated by conducting interviews in the form of confirmation to students. Based on the results and discussion obtained conclusion, that 100% of students at the age of concrete operation stage in this study already understand concept of eternity number. And 13.79% of students at the age of concrete operation stage in this study have had an understanding concept of eternity length.